The effect of plyometric training on the power-related factors of children aged 16 years-old: Plyometric training - Thaqi, Agron; Berisha, Milaim; Hoxha, Shkumbin (Progress in Nutrition, 2020)
Study Objectives: The purpose of this study is to determine the effects of a 12-week plyometric training program on the power (explosive force), acceleration, strength endurance and body extremities speed performance of children aged 16 years-old. Methods: The research was conducted on a sample of 220 male volunteer students (the sample divided in to the experimental and control group) aged 16 years ± 6 months, who are students of ‘’Fehmi Lladroci’’ high school from Glogoc, Republic of Kosovo. The tested plyometric training program was prepared according to the National Strength and Conditioning Association (NSCA) guides and applied 3-4 times per week (except for in the beginning and also in the last week of the program, where the program was applied twice a week). To process the results of the study, analysis of the data was done with the IBM SPSS Statistics 22 software. The statistics obtained were provided by two-way repeated analysis of variance (a repeated measure ANOVA). The development percentage in time were calculated by using the formula “%Δ = (x post-test – x pre-test) / pre-test *100” and values below p <0.05 were considered statistically significant. Results: According to the results of the study we observed that the plyometric training applied in the 12 week increased power performance (countermovement jump, standing broad jump, standing triple jump and standing medicine ball throw) by approximately 15-30%, acceleration performance (10 and 20 meter runs) by approximately 10-12%, lower and upper body extremities speed performance (plate tapping, and foot-tapping against the wall) by approximately 9-12% and strength endurance performance (sit-ups and push-ups in 30 secs) by approximately 40-45%. Conclusion: It was showed that the plyometric exercises applied to children aged 16 years-old increase the strength, acceleration and speed performance as well as the explosive force.